Time and poverty from a developing country perspective - Rania Antonopoulos; Emel Memis (Levy Economics Institute of Bard College, 2010)
This study is concerned with the measurement of poverty in the context of developing countries. We argue that poverty rankings must take into account time use dimensions of paid and unpaid work jointly. Reviewing the current state of the literature on this topic, our methodology introduces a critical but missing analytical distinction between time poverty and time deprivation. On this basis, we proceed to provide empirical evidence by using South African time use survey data compiled in 2000. Our findings show that existing methods that work well for advanced countries require modification when adopted in the case of a developing country. The results identify a group of adults who previously were inadvertently missing, as they were considered 'time wealthy.'
Keywords: J22; J16; I32; 330; time poverty measurement; time use; poverty; policy